First term: a1 = 151
common difference: d = -14 (we decrease by 14 each time, eg, 151-14 = 137)
nth term of this arithmetic sequence is...
an = a1+d(n-1)
an = 151+(-14)(n-1)
an = 151-14n+14
an = -14n+165
This will be used in the formula below
Sn = n*(a1+an)/2
<span>Sn = n*(151+(-14n+165))/2
</span><span>S26 = 26*(151+(-14*26+165))/2 ... replace every n with 26
</span>S26 = -624
The final answer here is choice C) -624
<span>
</span>
Answer:
Option 2.
Step-by-step explanation:
f(x) = - x^2 + 3
The parent function is x^2
- the '-' before the x^2 reflects it in the x-axis, and the + 3 shifts it up 3 units.
$7.90
Hope this helps!
Have a great day:)
Left 3 because the 3 is in the parenthesis